The effect of esg on financial performance among Malaysian public listed companies - Wong, Xen Yang (2023)
This thesis examines the relationship between Environmental, Social, and Governance (ESG) factors and financial performance among Malaysian public listed companies. The growing awareness of sustainability issues and the increasing demand for responsible corporate behavior have prompted organizations to incorporate ESG considerations into their strategic decision-making processes. This study aims to shed light on the potential impact of ESG practices on financial performance in the Malaysian context. The research adopts a quantitative approach, utilizing financial data and ESG ratings for a sample of Malaysian public listed companies over a specified time period. Multiple regression analysis is employed to explore the association between ESG performance and financial indicators such as return on assets, return of equity, Tobin’s Q ratio and stock return performance. The implications of this research contribute to the existing literature on ESG and financial performance by providing empirical evidence from the Malaysian context. The findings offer valuable insights for policymakers, investors, and corporate managers, emphasizing the importance of incorporating ESG considerations into decision-making processes. This study underscores the potential for sustainable business practices to create value not only for the environment and society but also for the financial performance of companies.